Role of sanitary and phytosanitary measures within the context of Free Trade Agreements - Torres, Alfonso (Revista Colombiana de Ciencias Pecuarias, 2013)
The international norms for the trade of animal products were implemented as part of the Marrakech Agreement that established the WorldTrade Organization (WTO) in 1995. This act culminated the negotiations maintained during the so called "Uruguay Round" (1986-1994) within the framework of the General Agreement on Tariffs and Trade (GATT) that included international trade norms for general merchandize but not for agricultural commodities.